Terras públicas para quem? o papel das terras de domínio da União na produção do espaço urbano em Fortaleza - Pompeu, Fernanda Frota (2022)
The weakening of the notion of the Welfare State, from the 1970s onwards, provoked changes in urban planning. The rationalist pattern, based on the ordering of land use and occupation, provided space to a more flexible planning model, aimed at producing immediate results, in which the interests of big capital are given a prominent role, making us reflect, therefore, about the role of the State in this new way of planning. Is the public interest being prioritized during the space production processes? The Federal Constitution of 1988 marked the brazilian legal framework, providing guidelines that prioritize the guarantee of this public interest. The principle of the social function of property, for example, emerged as a parameter in the identification and definition of the functions of public and private properties in meeting the social needs existing in cities. These functions must guide and reconcile the interest of the owner with the demands and social interests of the community, determined by the Municipal Master Plan. Public domain lands, as well as private lands, are also scenarios for the production of urban space and must fulfill their social function. In Brazil, the Union enjoys an immense real estate patrimony that must be destined to serve the public interest, fulfilling its social purpose. This work investigates the Union domain lands in the city of Fortaleza, seeking to understand how these lands have been occupied, and above all, the way the Union acts in the management of its properties. Is the principle of the social function of property being met? Therefore, in addition to the theoretical and conceptual review on the subject, the historical, legal-institutional and management contents were analyzed, favoring a spatial analysis of the information made available by the Secretary of Coordination and Governance of the Patrimony of the Union. The results point to the lack of adherence between the legal guidelines and the reality of the use and management of these lands in Fortaleza, confirming the proposition of recent Brazilian literature witch says that the collection function tends to be prioritized over the sociospatial aspects contained in the legislation.